Elucidation of molecular and hormonal background of early growth cessation and endodormancy induction in two contrasting Populus hybrid cultivars - Boldizsár, Ákos; Soltész, Alexandra; Tanino, Karen; Kalapos, Balázs; Marozsán-Tóth, Zsuzsa; Monostori, István; Dobrev, Petre; Vankova, Radomira; Galiba, Gábor (BMC plant biology, 2021)
BACKGROUND: Over the life cycle of perennial trees, the dormant state enables the avoidance of abiotic stress conditions. The growth cycle can be partitioned into induction, maintenance and release and is controlled by complex interactions between many endogenous and environmental factors. While phytohormones have long been linked with dormancy, there is increasing evidence of regulation by DAM and CBF genes. To reveal whether the expression kinetics of CBFs and their target PtDAM1 is related to growth cessation and endodormancy induction in Populus, two hybrid poplar cultivars were studied which had known differential responses to dormancy inducing conditions. RESULTS: Growth cessation, dormancy status and expression of six PtCBFs and PtDAM1 were analyzed. The 'Okanese' hybrid cultivar ceased growth rapidly, was able to reach endodormancy, and exhibited a significant increase of several PtCBF transcripts in the buds on the 10th day. The 'Walker' cultivar had delayed growth cessation, was unable to enter endodormancy, and showed much lower CBF expression in buds. Expression of PtDAM1 peaked on the 10th day only in the buds of 'Okanese'. In addition, PtDAM1 was not expressed in the leaves of either cultivar while leaf CBFs expression pattern was several fold higher in 'Walker', peaking at day 1. Leaf phytohormones in both cultivars followed similar profiles during growth cessation but differentiated based on cytokinins which were largely reduced, while the Ox-IAA and iP7G increased in 'Okanese' compared to 'Walker'. Surprisingly, ABA concentration was reduced in leaves of both cultivars. However, the metabolic deactivation product of ABA, phaseic acid, exhibited an early peak on the first day in 'Okanese'. CONCLUSIONS: Our results indicate that PtCBFs and PtDAM1 have differential kinetics and spatial localization which may be related to early growth cessation and endodormancy induction under the regime of low night temperature and short photoperiod in poplar. Unlike buds, PtCBFs and PtDAM1 expression levels in leaves were not associated with early growth cessation and dormancy induction under these conditions. Our study provides new evidence that the degradation of auxin and cytokinins in leaves may be an important regulatory point in a CBF-DAM induced endodormancy. Further investigation of other PtDAMs in bud tissue and a study of both growth-inhibiting and the degradation of growth-promoting phytohormones is warranted.
Keywords: Genes, Plant; PtCBFs; Gene Expression Profiling; Gene Expression Regulation, Plant; Plant Development; Plant hormone; rostlinné geny; vývoj rostlin; genetická variace; regulátory růstu rostlin; chiméra; Growth cessation; Gene expression; Genetic Variation; vegetační klid; Plant Dormancy; PtDAM1; Populus; Endodormancy; regulace genové exprese u rostlin; Chimera; stanovení celkové genové exprese; Plant Growth Regulators